Measures used to assess the burden of ESBL-producing Escherichia coli infections in humans: a scoping review. Issue 1 (14th February 2021) - McDonald, Kathryn L; Garland, Sarah; Carson, Carolee A; Gibbens, Kimberly; Parmley, E Jane; Finley, Rita; MacKinnon, Melissa C
Abstract: Background: ESBL-producing bacteria pose a serious challenge to both clinical care and public health. There is no standard measure of the burden of illness (BOI) of ESBL-producing Escherichia coli (ESBL-EC) in the published literature, indicating a need to synthesize available BOI data to provide an overall understanding of the impact of ESBL-EC infections on human health. Objectives: To summarize the characteristics of BOI reporting in the ESBL-EC literature to (i) describe how BOI associated with antimicrobial resistance (AMR) is measured and reported; (ii) summarize differences in other aspects of reporting between studies; and (iii) highlight the common themes in research objectives and their relation to ESBL-EC BOI. Methods and results: Two literature searches, run in 2013 and 2018, were conducted to capture published studies evaluating the BOI associated with ESBL-EC infections in humans. These searches identified 1723 potentially relevant titles and abstracts. After relevance screening of titles and abstracts and review of full texts, 27 studies were included for qualitative data synthesis. This review identified variability in the reporting and use of BOI measures, study characteristics, definitions and laboratory methods for identifying ESBL-EC infections. Conclusions: Decision makers often require BOI data to make science-based decisions for the implementation of surveillance activities or risk reduction policies. Similarly, AMR BOI measures are important components of risk analyses and economic evaluations of AMR. This review highlights many limitations to current ESBL-EC BOI reporting, which, if improved upon, will ensure data accessibility and usefulness for ESBL-EC BOI researchers, decision makers and clinicians.